Fantasy and Innovation in Deux pièces pour clavecin, h. 244 by Bohuslav Martinů - ICHIM, Diana; SZŐCS, Botond; DRĂGULIN, Stela (Studia Universitatis Babes-Bolyai Musica, 2024)
This article highlights the divergences between the historical and modern style of playing the harpsichord, through a detailed analysis of the album 2 Pièces pour clavecin, H. 244 by Bohuslav Martinů, a leading figure of 20th century cultural life. Given the abundance of baroque compositional means, this album of solo works for harpsichord, composed in 1935, represent the perfect combination between old and new, moreover, between tradition and innovation. The predilection for rediscovering Baroque music in its pure forms began in the 1900s and continues to this day, spreading with great speed thanks to the evolution of technology and numerous historical documents. Historical treatises, writings and numerous criticisms of Baroque performances have led performers towards the closest possible performance of early works, with emphasis on proper articulation type, dynamics, freedom in phrasing, construction and fingering. The harpsichord occupies a unique place in the chronicle of the renaissance of Early music, even if it was by no means the only ancient instrument to arouse new interest in the decades preceding the early 20th century. Looking at all these major changes, modern composers such as Arnold Schoenberg, Arthur Honegger, Darius Milhaud, Igor Stravinsky, Francis Poulenc, Philip Glass, Manuel de Falla and Bohuslav Martinů have revived the effervescent music of the Baroque.